2015
DOI: 10.1039/c5ra09686c
|View full text |Cite
|
Sign up to set email alerts
|

Properties of multi-phase foam and its flow behavior in porous media

Abstract: Aqueous foams were produced with partially hydrophobic SiO 2 nanoparticles and sodium dodecyl sulfate (SDS) dispersions. The injection behavior of SiO 2 stabilized foam (SiO 2 /SDS foam) was analyzed and compared with SDS stabilized foam (SDS foam). The experimental results showed that the SiO 2 nanoparticles and SDS surfactants had a synergistic effect on foam stability at proper SDS concentration. And the effect was although with a slight decrease of foam volume. The adsorption of nanoparticle on the bubble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Nevertheless, the foam is a kind of unstable thermodynamic system and a spontaneous process reduces the energy of the system. From the above analysis, it can be concluded that the foam is an unstable system, which determines relative stability of the foam itself [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the foam is a kind of unstable thermodynamic system and a spontaneous process reduces the energy of the system. From the above analysis, it can be concluded that the foam is an unstable system, which determines relative stability of the foam itself [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–7 ] A foam is made of gas bubbles dispersed in a continuous aqueous phase stabilized by surface active molecules adsorbed at the gas/liquid interface. [ 8,9 ] There are many ways to form foams, such as by gas entrainment or bubbling into the liquid, [ 10 ] or by the injection of gas and aqueous solution of surfactants into a porous medium [ 11,12 ] ; the latter strongly affects foam properties, in terms of microstructure and material.…”
Section: Introductionmentioning
confidence: 99%
“…16 The most commonly method for improving foam stability is addition of the so-called foam stabilizers to foam agent solutions. 17,18 Foam stabilizers are generally divided into two categories according to their function principles. One is to reduce the ability of CO 2 to permeate through foam lms, via increasing the amount of adsorbed surfactant at the foam lm by addition of some synergic agents, or via reducing the contact area of CO 2 -liquid phase by adding nanoparticles to the dispersion solutions.…”
Section: Introductionmentioning
confidence: 99%